On the effect of counterface materials on tribo-behavior of steel wire sliding under dry contact condition - Chee Su, Be; Ammar, Al Shalabi; B. F., Yousif (WORLD SCIENTIFIC PUBL CO PTE LTD, 2008)
Steel wires are implemented in numerous systems and undergo frequent faults due to tribological loading conditions. Therefore, this paper presents a study on the tribological performance of steel wire sliding against different counterfaces, namely, aluminum alloy, stainless steel, and mild steel using a block-on-ring tribo-tester. According to common mechanisms, the tests were performed under 5N applied load and 0.15m/s sliding velocity under dry contact condition. Additionally, scanning electron microscopy was used to examine the damaged features on the worn surfaces of the steel wire. Weight loss and friction coefficient results were presented versus sliding distances (0-1.6 km). In general, the results showed that friction coefficient did not reach the steady state due to the transformation of the wear mechanism from adhesive to abrasive mode. Nevertheless, the average of friction coefficient was found to be about 0.7 +/- 0.1 for stainless steel and 0.2 +/- 0.1 for mild steel. Weight loss gradually increased with the increase of sliding distance. The micrographs of worn surfaces revealed that the contact mechanism was transformed from adhesive to abrasive wear mode as implied by the scars and grooves on the wire surface.